Iraqi Invasion of Kuwait 1990, A Historical Study through the Newspaper "Lewaa Al Sader" - Al- Alawi, Nabeel (Al-Adab Journal, 2019)
The Iraqi-Iranian war resulted in many debts on Iraq, especially for Kuwait which supported Iraq financially and politically during the war. After the end of that war, Kuwait demanded the debts and also decided to increase its oil production which led to lower prices and a negative refections on the Iraqi economy. This urged the Iraqi president Saddam Hussein (1979-2003) to take an unthinkable decision to invade Kuwait by his forces on 2 August 199. Facing wide international condemnation, while the United States succeeded in mobilizing military forces in Saudi Arabia at the invitation from the latter, consisting of several countries that attacked Iraq and its military forces and liberated Kuwait on 27 February 1991. The Iraqi oppositions attitude towards the invasion and in particular the Supreme Council of the Islamic Revolution in Iraq was blaming both Iraq and Kuwait, as it opposed to the first and denounced the second for support Iraq during the Iraqi-Iranian war.